Students Perception Towards the Use of Sevima Edlink Platform in English Learning at Aquatic Resources Management - Armita Permatasari; Sri Rahayu Juniati; A. Fitriani (Universitas Muhammadiyah Enrekang, 2022)
This study aimed at investigating Students’ Perception towards the use of Sevima Edlink Platform in English Learning at Aquatic Resources Management Study Program at Universitas Muhammadiyah Sinjai. This research employed a quantitative research method with description survey. The population of this research consisted of 196 the first semester students of Agricultural faculty at Universitas Muhammadiyah Sinjai. This research used purposive sampling technique in choosing sample; the sample of this study was 30 students of Aquatic Resources Management study program Agricultural faculty. The researcher used questionnaire in collecting data. The used type of questionnaire in this research was open-ended questionnaire and close-ended questionnaire and the construct of the questionnaire used TAM theory. The data were analyzed by using descriptive statistics on SPSS. The result of this study showed that Edlink platform was application that can be used in online learning. This Edlink platform made it easy for students to work on and collect their assignments. Moreover, this Edlink platform had interesting features and was easy to learn. It made students become happy to use it. However, more specifically in learning English, this platform increase productivity in learning but this Edlink platform did not improve effectiveness in learning. Furthermore, it could still be recommended to others to use.